Stabilitas Dan Homogenitas Pewarna Alami Terenkapsulasi Dari Kunyit (Curcuma Domestica Val) Dalam Bentuk Cair Dan Serbuk - intan kusumaningrum (JURNAL AGROINDUSTRI HALAL, 2018)
The problem of using turmeric and other natural materials as a dye is the stability and homogeneity of the resulting colors. One effort to maintain the stability of pigments in turmeric is to do the coating (encapsulation) using a polymeric material. The purpose of this research is to know the stability and homogeneity of liquid dye and encapsulated turmeric powder. Liquid dye was obtained from turmeric extract which was done by evaporation process at 50ºC with addition of without liquid sugar and addition of 10% liquid sugar, while powder dye obtained from drying process with spray dryer with maltodextrin 10% and maltodextrin 20%. The stability of the color in the sample of liquid dye without sugar and with the addition of 10% liquid sugar has a bright L * (brightness), a * (red) and b * (yellow) color in the time period of day 0, day 30, 37th and 44th days, but the liquid dye with 10% liquid sugar has a brighter color than dye without gulacair. In powder dyes with 10% and 20% maltodextrin additions have a stable color of L * (brightness) and b * (yellow) at the time period of day 30, day 37 and day 44, while in a * red) of unstable powder sample where p> 0,05. The study used a complete randomized design with 2 replications. The homogeneity of color applied to the tofu shows a liquid dye without adding sugar and with the addition of 10% liquid sugar produces equally good and evenly distributed color homogeneity. Powder dye with the addition of 10% maltodextrin has better color homogeneity and is evenly distributed compared to 20% maltodextrin dye powder. Selected dyes are liquid dye with 10% liquid sugar and powder dye with maltodextrin 10%